Implementation of PSAK 107 and the Effect of Ijarah Financing on the Profitability of BPRS Amanah Ummah Leuwiliang Before and After the Covid-19 Pandemic Period - Hurriyaturrohman, Hurriyaturrohman; Wijayanti, Putriana; Indupurnahayu, Indupurnahayu; Sundarta, M.Imam (Moneter: Jurnal Keuangan dan Perbankan, 2024)
There are several Islamic private banks that have experienced setbacks in generating profits so that the assets and capital generated are not so good due to covid-19. Bank Amanah Ummah is experiencing declining profitability. The purpose of this study was to determine the effect of ijarah financing on the profitability before the covid-19 pandemic and afterwards of BPRS Amanah Ummah Leuwiliang. The data used are financial statements and interview results regarding the application of PSAK 107 for the 2017-2020 period. The data analysis method is simple linear regression using Microsoft excel 2010. Profitability is calculated by ROE net income divided by total equity. The results of this study indicate that ijarah financing has an effect on profitability before and after the pandemic, the ijarah financing scheme is sufficient to help the community, and the application of PSAK 107 regarding ijarah accounting is in accordance with the provisions.